2020
DOI: 10.3390/ma13245795
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Interlayer Temperature on Structure and Properties of Wire and Arc Additive Manufactured Duplex Stainless Steel Product

Abstract: WAAM (wire and arc additive manufacturing) is becoming an increasingly popular method to produce components from metals, which are usually not so suitable for conventional production methods. One of the good examples is duplex stainless steels (DSSs), which are quite complex for welding and machining. Excessive ferrite amount is a common problem for them and controlling an interlayer temperature could offer a solution. However, using too low interlayer temperature will slow down the whole process and compromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…A shielding gas flow of less than 10 L/min causes global or local porosity, as also observed by Knezović et al [55], where the groups of pores are on the outer sides of the duplex steel wall. The use of a flow of 12 L/min in combination with slag covering the face of the layer guarantees no porosity, except for the arc ignition point.…”
Section: Analysis Of Additive Manufacturing Processsupporting
confidence: 66%
See 1 more Smart Citation
“…A shielding gas flow of less than 10 L/min causes global or local porosity, as also observed by Knezović et al [55], where the groups of pores are on the outer sides of the duplex steel wall. The use of a flow of 12 L/min in combination with slag covering the face of the layer guarantees no porosity, except for the arc ignition point.…”
Section: Analysis Of Additive Manufacturing Processsupporting
confidence: 66%
“…Kozamernik et al [54] came to similar conclusions by examining the influence of the interpass temperature on the deviation from the geometry of the planned product, indicating that 150 • C is sufficient to obtain a deviation of less than 2%. Similarly, Knezović et al [55] indicate 150 • C as appropriate.…”
Section: Analysis Of Additive Manufacturing Processmentioning
confidence: 97%
“…In terms of the geometric point of view, Wang et al [15] showed that as the interlayer temperature increases, the width and height of the layer tend to enlarge and shorten, respectively. Furthermore, both Geng et al [10] (using an aluminium alloy) and Knezovic et al [16] (using duplex stainless steel) showed better surface finishing when higher levels of interlayer temperature were used, facilitating a possible machining step after deposition. However, this behaviour may not be the same for all materials, since Spencer et al [17] showed the opposite effect when a C-Mn steel was used as the feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The production of steel pipes is characterized by a relatively small amount of waste that is not recyclable and the need to use machines with a specialized structure and dimensions, or the technology used in the plant. Production takes place mainly with the use of electricity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%